A functional connectome: regulation of Wnt/TCF-dependent transcription by pairs of pathway activators. Issue 1 (December 2015) - Freeman, Jamie; Smith, David; Latinkic, Branko; Ewan, Ken; Samuel, Lee; Zollo, Massimo; Marino, Natascia; Tyas, Lorraine; Jones, Nick; Dale, Trevor
Abstract Background Wnt/β-catenin signaling is often portrayed as a simple pathway that is initiated by Wnt ligand at the cell surface leading, via linear series of interactions between 'core pathway' members, to the induction of nuclear transcription from genes flanked by β-catenin/TCF transcription factor binding sites. Wnt/β-catenin signaling is also regulated by a much larger set of 'non-core regulators'. However the relationship between 'non-core regulators' is currently not well understood. Aberrant activation of the pathway has been shown to drive tumorgenesis in a number of different tissues. Methods Mammalian cells engineered to have a partially-active level of Wnt/β-catenin signaling were screened by transfection for proteins that up or down-regulated a mid-level of TCF-dependent transcription induced by transient expression of an activated LRP6 Wnt co-receptor (∆NLRP). Results 141 novel regulators of TCF-dependent transcription were identified. Surprisingly, when tested without ∆NLRP activation, most up-regulators failed to alter TCF-dependent transcription. However, when expressed in pairs, 27 % (466/1170) functionally interacted to alter levels of TCF-dependent transcription. When proteins were displayed as nodes connected by their ability to co-operate in the regulation of TCF-dependent transcription, a network of functional interactions was revealed. In this network, 'core pathway' components (Eg. β-catenin, GSK-3, Dsh) were found to be the most highly connected nodes. Activation of different nodes in this network impacted on the sensitivity to Wnt pathway small molecule antagonists. Conclusions The 'functional connectome' identified here strongly supports an alternative model of the Wnt pathway as a complex context-dependent network. The network further suggests that mutational activation of highly connected Wnt signaling nodes predisposed cells to further context-dependent alterations in levels of TCF-dependent transcription that may be important during tumor progression and treatment.